Urban living labs as innovation infrastructure for local urban intervention acceleration and student social learning: the impacts on community wellbeing in Heerlen - Blezer, Stefano; Abujidi, Nurhan; Sap, Herwin (Frontiers in Public Health, 2024)
Cities are championing urban experiments in order to address societal challenges and increased urban complexity. In fact, and following fellow researchers, urban experiments are used as a method in a broader trend in public policy to align urban planning with citizen needs by viewing cities as platforms for societal transformation that require, and should draw on, active involvement of residents. In this study, we demonstrate the impacts of placemaking and Urban Living Labs not only for healthy environments but also in facilitating transdisciplinary learning. Therefore, we elaborate on the Aurora transformation process in the neighborhood GMS in Heerlen-North as being one of the 16 Dutch neighborhoods that need extra attention to its socio-urban challenges due to the historical context and consequent local development. Hence, providing two main results for ULLs as infrastructure for innovation for community wellbeing. First, as an alternative spatial planning approach for urban contexts with extreme social-urban conditions that draw on the multitude of local values to generate and accelerate urban transformations going beyond the traditional impacts of urban transformations including public health equity, health outcomes, and addressing social-economic determinants of community wellbeing. Second, as an infrastructure for education innovation encompassing and operationalising social learning theory. Subsequently, it addresses societal issues in these neighborhoods, such as loneliness, social exclusion, or democratic decision-making more appropriately and enhances student, and urban stakeholder, learning through transdisciplinary collaboration among those involved and by connecting education, research methods and questions, and real-life socio-urban challenges. We conclude the article by emphasizing its novelty, providing a discussion, and enumerating implications for theory, practice, policy, and research.